Functional Mobility and Balance After Total Hip Arthroplasty and Healthy Elders - Gholamhasan Mirzaei; Shohre Norizadeh Dehkordi; Masuod Nowrozi (University of Social Welfare & Rehabilitation Sciences, 2009)
Objectives: The purpose of this study was to determine the functional mobility and balance in the elders after Total Hip Arthroplasty in healthy coparison to elders. Methods & Materials: The current cross-sectional study was done on 20 patients (70.9±4.2) with hip osteoarthritis 6 months after Total Hip Arthroplasty and 20 healthy subjects (73±5.7) as control group. Patient group was assigned with nonprobability convenient samplingand control group selected with matched assignment. Functional mobility measured with Timed Up & Go Test, functional balance with Functional Reach and Berg Balance Scale and Functinal Activity Assesment measured with Modified Barthel Index. Independent T-test used for stastistical analysis. Results: Comparison between groups showed significantly longer time of Timed Up & Go test in patient group compared with control group (P<0.01). During FR in patient group the distance was significantly shorter than control group (P<0.01). Modified Bartel Index and the scores of Berg Bartel Scale in patient group were significantly less than control group (P<0.01). Conclusion: Results showed Significant decrease in functional mobility and balance in the elderly after Total Hip Arthroplasty compared towith control group